Pengaruh Workplace Bullying terhadap Organizational Citizenship Behavior yang Dimediasi oleh Job Satisfaction dan Resilience pada Seluruh Pegawai Puskesmas di Kota Banda Aceh - Syahirah, Nafla; Megawati, Megawati (Manajemen Inovasi Bisnis dan Strategi, 2025)
This research aims to examine the influence of Workplace Bullying on Organizational Citizenship Behavior which is mediated by Job Satisfaction and Resilience among all Public Health Center employees in Banda Aceh City. The sample used was 176 respondents. Data was obtained through distributing questionnaires. The data analysis technique used is Structural Equation Modeling (SEM) using SmartPLS3 software. The results of this analysis show that Workplace Bullying has a significant negative effect on Organizational Citizenship Behavior among Community Health Center employees in Banda Aceh City. Meanwhile, Job Satisfaction and Resilience mediate the influence of Workplace Bullying on Organizational Citizenship Behavior.Keyword: Workplace Bullying; Organizational Citizenship Behavior; Job Satisfaction; andResilience